The role of peer imitation in agricultural index insurance adoption: Findings from lab-in-the-field experiments in Kyrgyzstan - Laura Moritz; Lena Kuhn; Ihtiyor Bobojonov (Review of Development Economics, 2023)
Frequent climate shocks require farmers in developing countries to increase their resilience. Although index insurance is often discussed as a promising climate adaptation strategy, take-up rates are still low. This study primarily explores the role of peer behavior as peer imitation in the demand for three marketable and unsubsidized crop index insurance options. Furthermore, the influence of trust and understanding is investigated. We collected data in lab-in-the-field experiments among farmers in Kyrgyzstan, where index insurance is planned for imminent implementation. Applying ordered logit estimations, our results show significant and strong peer imitation effects. Imitation attitudes decrease with own insurance experience and received insurance payouts, but intensify with peer size, insurance trust and practical insurance understanding. While trust robustly increases index insurance adoption, understanding effects only gain significance in the dynamic perspective. These findings underline the importance of community-based extension treatments and trust toward the uptake of innovative agricultural technologies in the first steps of dissemination.
Keywords: G22; O12; O16; Q54; O30; Z13; 330; adoption behavior; agricultural index insurance; experimental economics; peer effects